Pengaruh Citra Merek, Nilai Utilitarian, Electronic Word of Mouth dan Kualitas Pelayanan terhadap Niat Beli Konsumen Miniso Ambarukmo Plaza Yogyakarta - Ambar Lukitaningsih; Nonik Kusuma Ningrum; Vivi Hastu Listyaningrum (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to examine the effect of brand image, utilitarian value, electronic word of mouth, and service quality on purchase intention. Purposive sampling was used in this study to select Miniso Ambarukmo Plaza Yogyakarta customers as the population of interest. Data for all Miniso Ambarukmo PlazaYogyakarta customers is collected through a survey. Use a Likert scale from 1 (strongly disagree) to 5 (strongly agree) to collect feedback using Google Forms (strongly agree). Multi-step linear regression analysis was used for processing. Utilitarian values ​​and Electronic Word of Mouth both have a positive and significant effect on Purchase Intention, according to the findings of this study. Brand Image has no effect on Purchase Intention with a significance value (0.100 > 0.05), but Utilitarian Value and Electronic Word of Mouth effect on Purchase Intention with a significan value (0.013 < 0.05) and (0.001 < 0.05) Service Quality has a positive and substantial effect on Purchase Intention, with a significance value (0.000 < 0.05). Keywords: brand image; utilitarian value; electronic word of mouth; quality of service; purchase intention